Analysis of heat shock protein genes expression in spruce bark beetle Ips typographus and their importance for survival upon exposure to heat - Švehlová, Kateřina (Jihočeská univerzita, 2012)
The aim of this work was to examine the expression of certain Hsp genes upon heat exposure in spruce bark beetle Ips typographus. We determined the level in unstressed and heat-exposed animals, and attempted to assess the importance of Hsp proteins for animals' survival upon heat treatment. We used RNA interference to knock down the expression of these genes, and analyzed the influence on animals exposed to elevated temperatures.
Analysis of heat shock protein genes expression in spruce bark beetle Ips typographus and their importance for survival upon exposure to heat
Keywords: Heat shock proteiny; RNA interfernece; Coleoptera; Ips typographus; Heat shock proteins; RNA interfernece; Coleoptera; Ips typographus